(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides a comparative analysis of the paralinguistic elements used in the English and Uzbek translations of Paulo Coelho’s “The Alchemist.” Paralinguistic devices, including tone, intonation, pauses, gestures, and physical actions, play a crucial role in fully conveying the content and emotional aspects of the work to the reader. During the research, these elements were categorized and analyzed based on the theories of scholars such as Crystal, Ekman, and Hofstede. The study results demonstrate that paralinguistic devices are consistently and purposefully applied in both the English and Uzbek translations, enabling the preservation of the text’s meaning within a new cultural context. This article aids in a deeper understanding of the importance of paralinguistic devices in the translation process and highlights their significance in literary translation.